Rohingya refugees and its impact on informal economy: Cox's Bazar, Bangladesh - Tanha, Moutusi; Siddique, Maliha Ahmed; Nurulhoque, Md.; Sumon, Md. Monirul Islam; Sazin, Rawshan; Hossain, Peas (Journal of Governance and Accountability Studies, 2023)
Purpose: The purpose of this study is to determine whether refugees in Cox's Bazar area of Bangladesh can successfully integrate into the informal economic sector. This evaluation was carried out by comparing the actions of refugees in the labor market with those of the local population. Research methodology: This study used survey data from two population groupings. The sample size included 300 Rohingya refugees and 300 locals from Coxs' Bazar, where they are now living. ANOVA was employed to compare the category mean differences owing to the limited sample size. The calculations would include wealth, occupation, language, religion, and race as labor market barriers. Results: The data indicated significant disparities in both types of occupations and monthly incomes between local workers and refugee workers. Furthermore, the findings also suggest that Rohingya refugees encounter greater challenges when entering the job market than local workers. Limitations: Refugees in Bangladesh are unable to work. They must stay at local and international NGO (Ministry of Foreign Affairs 2014). No Bangladeshi labor legislation has protected them. Bangladeshi authorities can also imprison refugees on illicit travel. A good Rohingya refugee policy in Bangladesh is crucial to human rights. Contribution: The Rohingya Muslim population in Myanmar has been subjected to genocide, resulting in their expulsion and subsequent migration to neighboring countries. Bangladesh is the primary host nation for the Rohingya group from Myanmar, which has sought safety there as refugees for many years. Due to their lack of legal employment opportunities in Bangladesh, these refugees engage in informal economic operations and participate in various criminal activities inside the place where they reside.